Early Onset Prosthetic Knee Joint Infection by Mycobacterium Fortuitum: A Case Report and Literature Review - Taweekitikul, MD, Pariwat; Ngarmukos, MD, Srihatach; Tanavalee, PhD, Aree (Journal of Southeast Asian Orthopaedics, 2022)
Prosthetic joint infection (PJI) is a devastating complication following total knee arthroplasty (TKA). Non-tuberculous mycobacteria (NTM) are considered a very rare cause of knee prosthetic joint infection with only a few of such cases reported in the literatures. Mycobacterium fortuitum is one of the NTM defined as rapidly growing mycobacteria (RGM). In this case report, we present an infected TKA case by M. fortuitum with an early onset of symptoms only 3 weeks from the index operation. Although the literature suggests two-stage exchange arthroplasty for surgical treatment in this group of patients, we could successfully treat this patient with debridement and prosthetic retention with the proper prolonged course of antibiotics. At 6-month follow-up, the patient revealed excellent functional outcomes with no signs of recurrent infection detected.